EFFECTIVENESS OF THE APPLICATION OF SOCIAL WELFARE INFORMATION SYSTEM – NEXT GENERATION (SIKS-NG) (STUDY IN BULUSIDOKARE VILLAGE, SIDOARJO REGENCY) - Nur Qomariyah, Halimatus Laili; Mursyidah, Lailul (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study evaluates the effectiveness of the Next Generation Social Welfare Information System (SIKS-NG) in managing Integrated Social Welfare Data (DTKS) at the village level, specifically in Bulusidokare Village, Sidoarjo Regency, as part of an e-government initiative by the Ministry of Social Affairs to improve the accuracy of social assistance targeting. Method: A qualitative descriptive approach with a case study design was employed, utilizing interviews, observations, and documentation, with analysis guided by Ricard M. Steers’ indicators of effectiveness: goal achievement, integration, and adaptation. Results: The findings indicate that SIKS-NG has been relatively effective in supporting accurate data updates and ensuring more targeted distribution of social assistance. The village government has demonstrated commitment through the appointment of competent operators and provision of adequate infrastructure. However, several challenges persist, including insufficient socialization from the Social Service, limited technical skills among some operators, and instances of inappropriate beneficiary proposals. Novelty: This research contributes a localized perspective by focusing on the implementation of SIKS-NG at the village level, an area that remains underexplored, thereby offering insights for strengthening e-government strategies in poverty alleviation at the grassroots level.